(untitled) (Global Journal of Human-Social Science, 2012)
This paper offers a broad retrospective on the experience of violence in international relations in Africa It advances several evidences to explain why the history of international relations had such a chequered history of international violence Increasing rate of violence within and among nation states have led to the widening of inequality gap between the poor and the rich countries of the world such that the campaign for liberal democracy by developed societies is now used as a tool to give human face to their imperial exploitation and domination This condition that places moral burden on the acclaimed relevance of international relations The international conditions which confirm the difficulty of this project also underscore its necessity The breakdown of European colonial empires and the increasing importance of the great powers to mould international affairs have resulted in an unruly world which contains a large number of small youthful nations with little experience in self-government and less in international affairs These nations often poor and frequently squabbling are the scene of enormous human suffering resulting from natural causes human incompetence or old-fashioned greed and viciousness The great powers themselves contribute in various ways to human anguish not least by maintaining the threat of nuclear war Their enormous power and wide ranging interests seem to have dulled their moral sensibility rather than the reverse Immense resources have allowed them to ignore the thinking of others and the genuine condition of the world as well as the real limitation of their own power- luxuries which other nations cannot afford Any effort such as this to explore resolution through critical content analysis and proffering the way forward underscores the necessity of this paper